Biomarker Preservation in Antarctic Sandstones after Prolonged Space Exposure Outside the International Space Station During the ESA EXPOSE-E Lichens and Fungi Experiment - Cassaro, Alessia; Pacelli, Claudia; Fanelli, Giuseppa; Baqué, Mickael; Maturilli, Alessandro; Leo, Patrick; de Vera, Jean Pierre Paul; Onofri, Silvano; Timperio, Annamaria (Astrobiology, 2025)
A primary aim of current and future space exploration missions is the detection and identification of chemical and biological indicators of life, namely biomarkers, on Mars. The Mars Sample Return NASA-ESA program will bring to Earth samples of martian soil, acquired from up to 7 cm depth. The ESA Rosalind Franklin rover will search for signs of life in the subsurface (down to a depth of 2 meters), given the highly radioactive conditions on Mars’ surface, which are not ideal for life as we know it and for the preservation of its traces. In the frame of the Lichens and Fungi Experiment, small fragments of Antarctic sandstones colonized by cryptoendolithic microbial communities were exposed to space and simulated martian conditions in low Earth orbit for 18 months, aboard the EXPOSE-E payload. Through the use of Raman and infrared spectroscopies, as well as a metabolomic approach, we aimed to detect organic compounds in a quartz mineral matrix. The results show that pigments, such as melanin, carotenoids, and chlorophyll, lipids, and amino acids, maintained their stability within minerals under simulated martian conditions in space, which makes them ideal biomarkers for the exploration of putative life on Mars.